PENGARUH BELANJA DAERAH TERHADAP PERTUMBUHAN EKONOMI KABUPATEN SUMBAWA TAHUN 2012–2018 - Ika Fitriyani; I Ismawati; Nurul Wahida; A Asmini (Jurnal Ekonomi & Bisnis, 2020)
This study aims to know how the influence of regional spending toward economic growth in Sumbawa district during the period of 2012-2018. This study was an associative study with a quantitative approach. The type of data used in this study was secondary data collected through the documentation method. The data collected were analyzed using simple linear regression analysis techniques, t test and the coefficient of determination (R2). Based on the results of study, obtained a simple linear regression equation, namely Y = 55.194 - 4.058 LnX + e, the constant value was 55.194. This constant value states that if the independent variable (regional spending) was equal to zero, then the economic growth in Sumbawa Regency will be 55.194 percent. Furthermore, the coefficient of determination was 0.255 percent. This showed that the realization of regional spending contributed 25.5 percent toward economic growth, while the remaining of 74.5 percent was influenced by variables outside the regression model of this study. Based on the results of research using the t test shows that the results obtained from regional spending with a t-value of -1.308 were lower than the t-table of 2.571, which means that there was no significant or no significant (negative) relationship between regional spending on economic growth in Sumbawa district.